(untitled) (Mustansiria Dental Journal, 2018)
Background: The aim of this study is to determine the relationship between the level of 8-hydroxydeoxyguanosine (8-OHdG) in saliva and severity of periodontal disease Material and method: Twenty five periodontitis patients were divided into two subgroups according to severity of periodontal disease (fifteen patients with probing pocket depth (PPD) <6mm and ten patients with PPD>6mm). Clinical examination which included measurement of both PPD and bleeding on probing (BOP) were carried out before and after initial periodontal treatment in addition to assessment of 8-OHdG in saliva and gingival crevicular fluid (GCF). Result: Salivary level of 8-OHdG in those with PPD >6mm was higher than those with PPD<6mm. Also this study evaluated 8-OHdG levels in GCF, it was detected only in periodontitis patients with PPD>6mm (mean PPD = 7.34) and only in some cases (4 out of 10). Conclusion: These data suggest that periodontally-involved teeth with deep pockets are a major source of salivary 8-OHdG levels may prove to be useful identifying patients with teeth of hopeless prognosis.